2013
DOI: 10.1242/dev.089524
|View full text |Cite
|
Sign up to set email alerts
|

Type Ib BMP receptors mediate the rate of commissural axon extension through inhibition of cofilin activity

Abstract: SUMMARYBone morphogenetic proteins (BMPs) have unexpectedly diverse activities establishing different aspects of dorsal neural circuitry in the developing spinal cord. Our recent studies have shown that, in addition to spatially orienting dorsal commissural (dI1) axons, BMPs supply 'temporal' information to commissural axons to specify their rate of growth. This information ensures that commissural axons reach subsequent signals at particular times during development. However, it remains unresolved how commiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…Taken together with our recent studies (Hazen et al, 2011; Yamauchi et al, 2008; Yamauchi et al, 2012), we have determined that these activities are differentially translated at both the receptor and second messenger level in dorsal spinal neurons. Thus, a shared activity of the type I Bmprs mediates the specification of the dorsal-most cell fates primarily through the Smad5 intermediate.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Taken together with our recent studies (Hazen et al, 2011; Yamauchi et al, 2008; Yamauchi et al, 2012), we have determined that these activities are differentially translated at both the receptor and second messenger level in dorsal spinal neurons. Thus, a shared activity of the type I Bmprs mediates the specification of the dorsal-most cell fates primarily through the Smad5 intermediate.…”
Section: Discussionsupporting
confidence: 65%
“…Thus, a shared activity of the type I Bmprs mediates the specification of the dorsal-most cell fates primarily through the Smad5 intermediate. In contrast, the activation of BmprIb alone regulates rate of growth of commissural axons, by activating Limk1 (Yamauchi, 2011) and (putatively) Smad1. Future studies will resolve whether Smad1 has a novel activity orchestrating cytoskeletal dynamics with Limk1 or whether the role of Smad1 reflects a requirement for transcriptional regulation during the formation of neural circuits.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies [3], [42], and those of others [43], [44], [45], [46], [47], [48] have shown that guidance factors can regulate the rate of axon extension by controlling the activity of cofilin and its negative regulator Limk1. Cofilin acts to depolymerize or sever actin [4].…”
Section: Discussionsupporting
confidence: 56%
“…Most of the data arise from studies of the sensory projection neurons of the spinal cord. BMP-7 and GDF-7 supplied by the roof plate orient axons of commissural neurons away from the roof plate and regulate their rate of extension through the spinal cord toward the floor plate (Augsburger et al, 1999; Butler and Dodd, 2003; Yamauchi et al, 2008, 2013; Sanchez-Camacho and Bovolenta, 2009). Guideposts are discrete groups of glial or neuronal cells that provide discontinuous information in intermediate positions along the path of growing axons (Sanchez-Camacho and Bovolenta, 2009).…”
Section: Bmps In Nervous System Development and Maintenancementioning
confidence: 99%